KETIDAKPUASAN CITRA TUBUH DAN PERILAKU DALAM MENURUNKAN BERAT BADAN PADA SISWI SMA DI SEMARANG - DIENNY, FILLAH FITHRA; KARTASURYA, MARTHA IRENE; PURUHITA, NIKEN (JNH (Journal of Nutrition and Health), 2014)
ABSTRACT Background : Adolescence is a period of growth spurt which result in the increase of nutritional needs. Physical and emotional changes often lead to body image dissatisfaction among adolescent girls.This study aimed to identify factors associated to body image and behaviors to reduce body weight among female students Methods : This survey study used a cross sectional design, with quantitative approach. This study was conducted on female students at SMAN 3 Semarang. The selection of 107 subjects was performed by stratified random sampling technique. Data on age, family characteristics, peer group influence, body image, motivation and behaviors to achieve ideal body shape collected by interviews using structured questionnaire. Weight, height and percent body fat were measured by Bio Impedance Analyzer (BIA) and microtoise. Data were analyzed by person Product Moment, Rank Spearman correlation tests and multiple liniar regression method. Results: Subjects aged 14-17 years old. One poin nine percents of subjects were obese, and 5.6% were overweight. Forty six point seven percents of the subjects were dissatisfied of their body image, eventhough 38 subjects of them were classified as normal and 7 subjects were underweight. Total of 68.2% of the subjects desired tall and slim body shape. Total of 50.4% subjects had made efforts to reach the ideal body shape in many ways, such as excessive diet (22.2%), consumption of drugs/ slimming tea (9.3%), excessive diet and exercise (37%). Percent body fat and peer group influence were the most affected factors on body image dissatisfaction. There was a possitive correlation between body image, motivation and the inappropriate behaviors to reach the ideal body shape among adolescence. Conclusions: Percent body fat and peers group influence affected body image dissatisfaction, which in turn increasing motivation in doing inappropriate behavior to attain the ideal body shape among female students. Keyword : body image dissatisfaction, behavior, body weight, adolescent ABSTRAK Latar Belakang    : Masa remaja merupakan periode percepatan petumbuhan dan perkembangan sehingga kebutuhan gizi meningkat. Perubahan fisik dan emosi yang tidak stabil seringkali menimbulkan ketidakpuasan citra tubuh di kalangan remaja putri. Penelitian ini bertujuan mengidentifikasi faktor yang berhubungan dengan citra tubuh dan perilaku dalam menurunkan berat badan pada remaja putri Metode : Penelitian survei ini dilakukan dengan desain cross sectional melalui pendekatan kuantitatif. Populasi adalah siswi SMAN 3 Semarang. Pemilihan 107 subjek dilakukan dengan rancangan stratifikasi sederhana. Data usia, karakteristik keluarga, pengaruh teman sebaya, citra tubuh, motivasi dan perilaku pencapaian bentuk tubuh ideal diperoleh melalui wawancara dengan kuesioner. Berat badan, tinggi badan dan persen lemak tubuh diukur menggunakan Bio Impedance Analyzer dan microtoise. Data dianalisis dengan uji korelasi Product Moment dari Pearson, Rank Spearman dan regresi linier berganda. Hasil : Subjek berusia 14-17 tahun. Sebesar 1,9 % subjek mengalami obesitas, dan 5,6% kelebihan berat badan. Sebanyak 50 subjek (46,7%) mengalami ketidakpuasan citra tubuh, padahal 38 subjek diantaranya berstatus gizi normal dan 7 subjek tergolong kurang, 68,2% menginginkan bentuk tubuh tinggi langsing, dan 50,4% pernah melakukan upaya pencapaian bentuk tubuh ideal secara tidak tepat, antara lain diet yang salah (22,2%), konsumsi obat/teh pelangsing (9,3%), diet dan olahraga berlebih (37%). Persen lemak tubuh dan pengaruh teman sebaya merupakan faktor yang paling berpengaruh terhadap ketidakpuasan citra tubuh. Ada hubungan positif antara ketidakpuasan citra tubuh dan motivasi dengan perilaku tidak tepat dalam pencapaian bentuk tubuh idea remaja. Simpulan : Persen lemak tubuh dan pengaruh teman sebaya berpengaruh terhadap ketidakpuasan citra tubuh. Selanjutnya ketidakpuasan citra tubuh meningkatkan motivasi remaja putri untuk melakukan upaya pencapaian bentuk tubuh ideal secara tidak tepat.